Phytoplankton dynamics in nearshore regions of the western Antarctic Peninsula in relation to a variable frontal zone in the Gerlache Strait - Mascioni, Martina; Almandoz, Gastón O.; Cusick, Allison; Pan, B. Jack; Vernet, Maria (Frontiers in Marine Science, 2023)
The Gerlache Strait is a narrow channel that separates the western coast of the Antarctic Peninsula (WAP) from the Palmer Archipelago. This area is characterized by the presence of interconnected fjords, bays, islands, and channels that serve as a refuge for megafauna during summer. Through the framework of FjordPhyto – a citizen science collaboration with the International Association of Antarctica Tour Operators (IAATO) vessels – we assessed phytoplankton biomass and composition in surface waters of six under-explored nearshore areas connected to the Gerlache Strait (between 64° and 65° S) during three consecutive seasons, from November to March (2016–2019). During the first two seasons, we found significant differences in the phytoplankton community distribution and successional patterns to the north and south of the sampling area; the greatest differences were evidenced mainly in the months of high biomass, December and January. During December, cryptophytes bloomed in the north, while microplanktonic diatoms dominated in the south, and during January, small centric diatoms dominated in the north, while prasinophytes bloomed in the south. This spatial distinction in phytoplankton communities were mainly associated with the occurrence of a surface thermal front in the Gerlache Strait around 64.5° S. The presence of the front separating warm waters to the north and colder waters to the south, during the months of December to February, was confirmed by the analysis of 10 years of remote sensing data. By contrast, during the third season, low biomass prevailed, and no differences in the phytoplankton composition between the north and south areas were observed. The third season was the coldest of the series, with smaller differences in water temperature north and south of the usual front location. This study shows for the first time a complete overview of the phytoplankton composition throughout the entire growth season (November through March) in the nearshore areas of the WAP between 64° and 65° S. The results of this work contribute to the understanding of the phytoplankton community in relation to small scale physical features during the Antarctic austral summer.